Action research (Utah : Linton Professional Development Corporation, 2002)
Program 1: Action research to impact practice ; program 2: Doing action research
program 1 Action research to impact practice - program 2 Doing action research
Presenter: Cathy Caro-Bruce
Keywords: Action research; Action research in education